PENGENALAN GAYA PENGASUHAN DAN PENINGKATAN PANTAU PERTUMBUHAN ANAK USIA SEKOLAH DASAR - Angkasa, Dudung; Rozali, Yuli Azmi; Vionalita, Gisely (Jurnal Pengabdian Masyarakat AbdiMas, 2022)
SDN Kedaung Barat 1 has no specific room for performing a UKS (school health services) activities. Hence, growth monitoring program is rarely performe in a regular basis. UKS also may help the school society including parents to involve actively to its program and build a holistic nutrition and health program for the students. This community service aimed at enhancing the growth measurement skills and also parenting style. Representative of teacher, student and parents were involved in this activities. Participants were enthusiatic with the given educational materials. Question and answer cames from participant during discussion about the parenting styles and growth monitoring as well. Student also had a change to speak up about how they parents behave to them. This activity enabled the participant to identify why school children did not gain weight or height rapidly. Participants also gained a technical skills to measure the growth accurately and at the same time how to calibrate the measurement tools particularly the digital weighing scale. This community service activity was reported in local media mass and had been posted in a youtube channel https://youtu.be/ENqGMNrvC7k and instagram @giselprogram.